THE INFLUENCE OF E-COMMERCE, SHARIA FINANCIAL INCLUSION, AND HALAL CERTIFICATION ON THE DEVELOPMENT OF CULINARY MSMES IN MEDAN CITY - Pasaribu, Syafita Khairunnisa; Sugianto; Juliana Nasution (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
This study explores the impact of e-commerce, Islamic financial inclusion, and halal certification on the development of culinary Micro, Small, and Medium Enterprises (MSMEs) in Medan City. As digital transformation becomes increasingly vital for business growth, especially among MSMEs, the study emphasizes the role of technological adoption and product legitimacy in enhancing competitiveness. Using a quantitative method with multiple linear regression analysis, data were collected from 60 MSME actors in East Medan through structured questionnaires. The results show that e-commerce and halal certification have a significant and positive effect on MSME development, while Islamic financial inclusion does not demonstrate a significant impact. These findings suggest that digital platforms and halal certification are crucial drivers for business growth, whereas further efforts are needed to improve awareness and access to Islamic financial services. The study highlights the need for continuous technological utilization and regulatory support to enhance the sustainability and competitiveness of MSMEs in the halal economy sector.